The Human Cost of Global Internship Mobility: Lessons From The Ferienjob Program In German - Al Syaqina, Nasyiha; Juwita Septiani, Putri; Rogida, Rezza; Lestari, Via Ayu (Candidate: Jurnal Sains Politik, 2025)
The international internship program, examined through the case study of the Ferienjob in Germany from October to December 2023, involved thousands of Indonesian university students. These students were promised internship opportunities in Germany; however, the reality of the program did not align with those promises. Many students were found to be working in non-procedural conditions, ultimately leading them to feel exploited. The findings of this study highlight the crucial role of both the government and universities in ensuring safe and supportive working environments, as well as in strengthening protections for student participants. Using a qualitative research method and descriptive analysis, this study identifies key challenges faced by interns, including the mismatch between expectations and actual working conditions, as well as the lack of support from organizing institutions.